The optimal height of aggregated steel beams - Truong, Bui Quang (Vietnam Journal of Mechanics, 1992)
The author proposes a method to find out the optimal height of aggregated steel beam and the general formula to calculate the height which fully meets the hard and depends on load-form and link together in two ends of the beam.